Desain dan Performansi Turbin Ventilator Angin Yang Dibuat dari Generator Sepedamotor - Indro, M.N.; Sumaryada, T.; Lyjamil, V.N.H. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
In this paper we present our research on the design and performance of ventilator wind turbine. The generator for the wind turbine was taken from a used motorcycle’s generator. The weight of this generator has to be reduced almost a half from its previous weight (from 0.80 kg to 0.40 kg), otherwise the wind turbine will not rotate at all. The generator consist of 8 coils arrange in north-south pole adjacently. By varying the number of turns in each coils we could check the performance of the turbine in medium and fast wind speed. our results show that the output power of the ventilator wind turbine depend linearly on the number of turns and the wind speed. For medium wind speed (4 m/s), the highest efficiency is found to be 2.4 % with the output current and voltage are 24.33 mA and 6.00 Volt consecutively. For high wind speed (5 m/s), the highest efficiency is found to be 2.9 % with the output current and voltage 40.43 mA and 8.50 Volt. Some suggestions to increase the performance of the ventilator wind turbine were also given in this paper. Key words : motor cycle’s generator, output current-voltage, wind turbin ventilatur.